Enhancing Moral Agency: Clinical Ethics Residency for Nurses - Robinson, Ellen M. (The Hastings Center report, 2014)
One antidote to moral distress is stronger moral agency—that is, an enhanced ability to act to bring about change. The Clinical Ethics Residency for Nurses, an educational program developed and run in two large northeastern academic medical centers with funding from the Health Resources and Services Administration, intended to strengthen nurses’ moral agency. Drawing on Improving Competencies in Clinical Ethics Consultation: An Education Guide, by the American Society for Bioethics and Humanities, and on the goals of the nursing profession, CERN sought to change attitudes, increase knowledge, and develop skills to act on one's knowledge. One of the key insights the faculty members brought to the design of this program is that knowledge of clinical ethics is not enough to develop moral agency. In addition to lecture-style classes, CERN employed a variety of methods based in adult learning theory, such as active application of ethics knowledge to patient scenarios in classroom discussion, simulation, and the clinical practicum. Overwhelmingly, the feedback from the participants (sixty-seven over three years of the program) indicated that CERN achieved transformative learning.